Hullabaloo in the guava orchard - Desai, Kiran 1971- (New York, NY Atlantic Monthly Press, 1998)
Fired from his job, the good-for-nothing Indian postal clerk, Sampath Chawla, 20, climbs a guava tree in search of contemplation and becomes a famous holy man. All of which proves his grandmother's point that the world is round and what goes downhill often emerges on top at the other end. A first novel.
Keywords: Roman de l'Inde de langue anglaise - Inde - 20e siècle; Sadhus -- India -- Fiction; Inde - Romans; India -- Fiction; Humorous fiction